KAJIAN DATABASE KEANEKARAGAMAN HAYATI KOTA SEMARANG - Edi Suwarso; Dicky Rizaldi Paulus; Miftachurahma Widanirmala (Jurnal Riptek, 2019)
Realization of sustainable development in the city of Semarang, as city that among 100 cities labeled as “Resilient city” had done the mapping of its’s regional biodiversity information. The purpose of this project was to provide information related to flora and fauna to all who require such information especially for the purpose of development of Semarang. The collected database will be aimed to help the development of City of Semarang that does not disregard the existence of its biodiversity, especially key species and endemic species. Biodiversity is any living form in aerial ecosystem, terrestrial ecosystem and aquatic ecosystem, both plants and animals, as well as microorganism. Indonesia, as a tropical country, is a biodiversity hotspot even when we compare to other tropical countries. Within every region, exist high number of biodiversity due to unique characteristic of its environmental conditions. The city of Semarang itself is a mixture of various ecosystem ranging from mountainous and hills to flat land and sea, both urbanized and natural landscape; therefore, resulting in high number of biodiversity in Semarang. Unfortunately, this biodiversity condition was not well documented, thus it is neglected and buried under the rapid development and urbanization of the city of Semarang. Development in both rapid and slow pace not only will have positive impact, but also negative impact, one of them is loss of biodiversity. This project was done to complete and update the biodiversity database and information especially organism that can be used to indicate certain environmental condition by applying principle of VES (Visual Encounter Survey) in Line Transect method and Point Count method. This project was resulted in findings of 10 species of Mammals, 78 species of Birds, 26 species of Herpetofauna, 86 species of Insects (butterflies and dragonflies), and 19 species of fish.